Switch‐and‐examine combining with different new switch statistics for diversity over Rayleigh fading channels. (9th October 2012) - Chau, Yawgeng A.; Chen, Yao‐Hua
SUMMARY Three schemes of multibranch switch‐and‐examine combining (MSEC) with switch statistics different from the signal‐to‐noise ratio used in the traditional MSEC are analyzed. For each diversity branch, with its fading factor a and low‐passed received signal r, the switch statistics for the three MSEC schemes considered in the paper are | r | , | ar | , and a linear combination of a and | r | , respectively. To illustrate the performances of the MSEC schemes, the average BER of each MSEC scheme with BPSK signaling is evaluated for independent and identically distributed Rayleigh fading channels. For performance optimization, the optimal switch thresholds of the MSEC schemes are obtained. Numerical results based on the analysis and simulations are presented for performance illustrations. Copyright © 2012 John Wiley & Sons, Ltd.